Particle deposition and aggregation measurement, modelling, and simulation - Elimelech, M. (Colloid & Surface Engineering)
Deposition and aggregation of small solid particles are encountered in many natural and industrial environments. Whether it be deposition of particles onto a surface immersed in a liquid suspension or aggregateion of individual particles, these processes.